Eleanor & Park [compact disc, unabridged] - Rowell, Rainbow (Listening Library, 2013)
Set over the course of one school year in 1986, this is the story of two star-crossed misfits--smart enough to know that first love almost never lasts, but brave and desperate enough to try.